Early intracranial haemorrhages in acute promyelocytic leukaemia: analysis of neuroradiological and clinico‐biological parameters. (10th August 2020) - Gurnari, Carmelo; Breccia, Massimo; Di Giuliano, Francesca; Scalzulli, Emilia; Divona, Mariadomenica; Piciocchi, Alfonso; Cicconi, Laura; De Bellis, Eleonora; Venditti, Adriano; Del Principe, Maria Ilaria; Arcese, William; Lo‐Coco, Francesco; et al.
Summary: Acute promyelocytic leukaemia (APL) represents a modern success of precision medicine. However, fatalities occurring within the first 30 days of induction treatment, in particular intracranial haemorrhage (ICH), remain the main causes of death. We studied the clinico‐biological characteristics of 13 patients with APL who experienced ICH. Compared to 85 patients without this complication, patients with ICH were older and more frequently had high‐risk APL. Moreover, positivity for the 'swirl' sign at neuroradiological imaging and hydrocephalus were predictors of a fatal outcome, together with lower fibrinogen, prolonged international normalized ratio (INR) and higher lactate dehydrogenase levels.